The Influence of Leadership and Work Motivationon The Work Spirit of Employees in Regional Secretariat of Sumenep District - Nuning Nurna Dewi (Institute of Computer Science (IOCS), 2021)
In the case of the Regional Secretariat of Sumenep Regency, the change of new leadership who has charisma, special quality, power and assertiveness that is different from the old leader has resulted in adjustments in leadership styles and styles so that it affects work procedures and motivation in performing tasks where generally employees tend comparing the attitudes, behavior and motivation of the old leader with the new leader so that it will determine whether they have a different impact on individual tasks and group assignments in performing tasks. This means that the leadership at the Regional Secretariat Kab. Sumenep has provided direction and guidance so as to create a conducive atmosphere and work motivation for the lowest item, namely satisfaction with the work environment is actually adequate but there are still needs for changes such as expansion of the workplace due to the large number of employees, office renovation because office buildings are classified as old buildings and as the producer of the District Secretariat. Sumenep is placed in a more strategic place and can be easily reached by taxpayers.